Inducing Social Norms in Laboratory Allocation Choices - Schram, Arthur; Charness, Gary (Management science, 2015)
Social norms involve observation by others and external sanctions for violations, whereas moral norms involve introspection and internal sanctions. To study such norms and their effects, we design a laboratory experiment. We examine dictator choices, where we create a shared understanding by providing advice from peers with no financial payoff at stake. We vary whether advice is given, as well as whether choices are made public. This design allows us to explicitly separate the effects of moral and social norms. We find that choices are in fact affected by a combination of observability and shared understanding. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2073 . This paper was accepted by Teck-Hua Ho, behavioral economics .